2006
DOI: 10.1038/nrn1888
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlations, population coding and computation

Abstract: How the brain encodes information in population activity, and how it combines and manipulates that activity as it carries out computations, are questions that lie at the heart of systems neuroscience. During the past decade, with the advent of multi-electrode recording and improved theoretical models, these questions have begun to yield answers. However, a complete understanding of neuronal variability, and, in particular, how it affects population codes, is missing. This is because variability in the brain is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

62
1,534
4
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,559 publications
(1,607 citation statements)
references
References 67 publications
62
1,534
4
7
Order By: Relevance
“…AC had relatively weak coupling and a short timescale (hundreds of milliseconds), which might aid representations of rapidly fluctuating stimuli and high dimensional sensory features. Previous studies have proposed that noise correlations can have a detrimental, information-limiting effect 23,26,29 and have thus suggested that sensory codes may benefit from weak coupling, which appears consistent with our findings in AC. However, in contrast, PPC had strong coupling and a long population timescale (~1 s), which appear to have a beneficial effect because higher levels of coupling and temporal information consistency corresponded to accurate task performance.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…AC had relatively weak coupling and a short timescale (hundreds of milliseconds), which might aid representations of rapidly fluctuating stimuli and high dimensional sensory features. Previous studies have proposed that noise correlations can have a detrimental, information-limiting effect 23,26,29 and have thus suggested that sensory codes may benefit from weak coupling, which appears consistent with our findings in AC. However, in contrast, PPC had strong coupling and a long population timescale (~1 s), which appear to have a beneficial effect because higher levels of coupling and temporal information consistency corresponded to accurate task performance.…”
supporting
confidence: 92%
“…To examine the structure of functional interactions in population activity 18,2327 , we modified our encoding model to predict a given neuron’s activity based on the past activity of each of the other imaged neurons (“coupling predictors”; activity from up to ~2 s in the past, within defined lag ranges). These coupling predictors were included in a single model along with the task-related predictors described above 20 (“task predictors”; Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several measures, such as Mutual Information, Fischer information and coherence (for an overview, see, e.g. Averbeck et al 2006), have been used to quantify the amount of information in the input and output. These studies have provided a thorough overview of the neuronal properties and of the neural encoding of information that is critical for reliable information transmission (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Averbeck and colleagues investigated how neural activity in PFC evolves as the monkey gradually acquires knowledge of the correct movement sequence and found that the sequence predicted by neuronal activity changes gradually from the sequence that had been correct in the previous block to the sequence that is correct in the current block. They showed that the information coded in the ensemble neuronal activity about the correct sequence increases as the monkey discovers it [62] .…”
mentioning
confidence: 99%